Tacrolimus and corticosteroids can live together. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Dermatologists tend to apply percutaneously whatever drug is effective on skin disorders when given systemically. This is why, in 1952, a few years after the appearance of systemic corticosteroids, Sulzberger and Witten (17) published the first report on the effectiveness of topically applied hydrocortisone acetate on atopic dermatitis. In the following 25 years two contrasting tentences were observed. On one hand, in the wake of the initial enthusiasm caused by the revolutionary new treatment, new increasingly powerful molecules were synthesized, through fluorination, acetylation, esterification and double-bound induction. On the other hand, the side-effects of the new molecules were reported. The latter were responsible for a prejudicial fear against corticosteroids till the actual corticophobia.